KETERKAITAN ANTARA MOTIVASI, KEPERCAYAAN, NORMA SUBYEKTIF, SIKAP DAN NIAT UNTUK BERBAGI PENGETAHUAN - Tantri Yustina; Mugi Harsono (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
The purpose of this study is to examine and analyze the effect of extrinsic motivation, intrinsic motivation, subjective norms, trust, and attitudes toward intention for sharing knowledge. Type of the research in this study is a quantitative reserch, by taking samples 200 respondents at SMP Muhammadiyah and MTs Muhammadiyah at Sukoharjo. The technique of collecting data uses questionnaires, and tested uses structural equation model/Structural Equation Modelling (SEM). The results of this study show that extrinsic motivation and intrinsic motivation has no effect on the intention to share knowledge, extrinsic motivation and intrinsic motivation effect on attitudes and trust, trust and subjective norms effect on attitudes and attitudes, and subjective norms effect on the intention for sharing knowledge. Key words : extrinsic motivation, intrinsic motivation, subjective norms, beliefs, and attitudes toward the intention for sharing knowledge